Strain shielding in distal femur after patellofemoral arthroplasty under different activity conditions - Meireles, Susana (2010)
Strain shielding, a mechanical effect occurring in structures combining stiff with more flexible materials, is considered to lead to a reduction of density in bone surrounding the implant. This effect can be related to the weakness of the implant fixation, which can promote implant loosening. Several studies describe a significant decrease in postoperative bone mineral density adjacent to joint implants, which can compromise their long-term fixation. The aim of the present Study was to quantify the strain shielding effect on the distal femur after patellofemoral arthroplasty. For this purpose three activities of daily living were considered: level walking, stair climbing and deep bending at different angles of knee flexion. To determine the strain shielding effect, cortical bone strains were measured experimentally with triaxial strain gauges in synthetic femurs before and after patellofemoral arthroplasty for each of the different daily activities. The results showed that the patellofemoral arthroplasty in general reduced the strains in the medial and distal regions of the femur when deep bending activity occurred, consequently, strain shielding in these regions, with Strain decreases of -72.0% and -67.5% were measured. On the other side, higher values of strain were found in the anterior region after patellofemoral replacement for this activity with an increase of +182.0%. The occurrence of strain shielding seems to be more significant when the angle of knee flexion and applied load increases. Strain shielding and over-loading may have relevant effects on bone remodeling surrounding the patellofemoral implant, suggesting a potential effect of later bone resorption in the medial and distal femur regions in case of regular deep bending activity.